Adjuvant Radiotherapy in Stage II Endometrial Cancer: Selective De-intensification of Adjuvant Treatment. Issue 1 (January 2023) - Paulson, K.; Logie, N.; Han, G.; Tilley, D.; Menon, G.; Menon, A.; Nelson, G.; Phan, T.; Murray, B.; Ghosh, S.; Pearcey, R.; Huang, F.; et al.
Abstract: Aims: Risk stratification, including nodal assessment, allows for selective de-intensification of adjuvant radiotherapy in stage II endometrial cancer. Patterns of treatment and clinical outcomes, including the use of reduced volume 'mini-pelvis' radiotherapy fields, were evaluated in a population-based study. Materials and methods: All patients diagnosed with pathological stage II endometrial cancer between 2000 and 2014, and received adjuvant radiotherapy in a regional healthcare jurisdiction were reviewed. Registry data were supplemented by a comprehensive review of patient demographics, disease characteristics and treatment details. The Charlson Comorbidity Score was calculated. Survival and recurrence data were analysed. Results: In total, 264 patients met the inclusion criteria. Most patients had endometrioid histology (83%); 41% of patients had International Federation of Gynecologists and Obstetricians grade 1 disease. Half (49%) had surgical nodal evaluation; 11% received chemotherapy. Most patients (59%) were treated with full pelvic radiotherapy fields ± brachytherapy. Seventeen per cent of patients received mini-pelvis radiotherapy ± brachytherapy, whereas 24% received brachytherapy alone. Five-year recurrence-free survival was 87% for the entire cohort, with no significant difference by adjuvant radiotherapy approach. Only one patient receiving mini-pelvis radiotherapy ± brachytherapy recurred in the pelvis but outside of the mini-pelvis field. Recorded late toxicity rates were highest for full pelvis radiotherapy + brachytherapy. Conclusion: Risk stratification in a real-world setting allowed for selective de-intensification of adjuvant radiation with equivalent outcomes for stage II endometrial cancer. Mini-pelvis radiotherapy combined with brachytherapy is effective in highly selected patients, with the potential to decrease toxicity without compromising local control. Brachytherapy should be considered in low-risk stage II patients. Highlights: Population outcomes for adjuvant radiotherapy in stage II endometrial cancer. Risk stratification in a real-world setting allows for selective de-intensification with equivalent outcomes. Mini-pelvis radiotherapy + brachytherapy boost, and brachytherapy alone, are effective adjuvant radiation options for selected Stage II endometrial cancer.